The Republic of Türkiye's Diplomatic Stance from the Perspective of Public Diplomacy and its Response to Disinformation: Israeli-Palestinian Conflict - Ahmet Koçyiğit (Erciyes İletişim Dergisi, 2024)
Today, disinformation has an impact on all aspects of political communication. Public diplomacy is the most important of them. In this context, the Republic of Türkiye has established the Directorate of Communications, Center for Countering Disinformation. It is aimed to develop an effective strategy to combat disinformation both nationally and internationally. This study is centered on the Republic of Türkiye's combat against disinformation in the international arena, within the context of public diplomacy. In this respect, the study aims to reveal the Republic of Türkiye's response and diplomatic stance against disinformation from the perspective of public diplomacy in the Israeli-Palestinian conflict. In line with this objective, a total of 110 pages of disinformation bulletins published in English by the Center for Countering Disinformation on the Israeli-Palestinian war, including its 99th and 102nd issues, were analyzed with content analysis method using the MAXQDA 2022 package program. As a result of the research, it was determined that the Center for Countering Disinformation, through its bulletins, has made a concentrated effort to combat fake news and allegations about the Israeli-Palestinian conflict in both traditional and digital media. Moreover, disinformation bulletins addressed manipulated, fabricated, fake, and parody content the most.